Leveraging insights into cancer metabolism—a symposium report. Issue 1 (2nd December 2019) - Cable, Jennifer; Finley, Lydia; Tu, Benjamin P.; Patti, Gary J.; Oliver, Trudy G.; Vardhana, Santosha; Mana, Miyeko; Ericksen, Russell; Khare, Sanika; DeBerardinis, Ralph; Stockwell, Brent R.; Edinger, Aimee; et al.
Abstract: Tumor cells have devised unique metabolic strategies to garner enough nutrients to sustain continuous growth and cell division. Oncogenic mutations may alter metabolic pathways to unlock new sources of energy, and cells take the advantage of various scavenging pathways to ingest material from their environment. These changes in metabolism result in a metabolic profile that, in addition to providing the building blocks for macromolecules, can also influence cell signaling pathways to promote tumor initiation and progression. Understanding what pathways tumor cells use to synthesize the materials necessary to support metabolic growth can pave the way for new cancer therapeutics. Potential strategies include depriving tumors of the materials needed to grow or targeting pathways involved in dependencies that arise by virtue of their altered metabolis.